Praktek Perubahan Akad Musyarakah Di BSI KC Bandar Jaya Perspektif Hukum Islam - Hauriyah, Ida Khoridah; Febriana, Nabilah; Sulistyani, Ambar (Universitas Islam Negeri Raden Intan Lampung, 2023)
As a financial institution, Bank Syariah Indonesia (BSI) KC Bandar Jaya has customers who do not pay installments every month. The problem under study is what are the factors causing the addendum to the musyarakah contract at Bank Syari'ah Indonesia (BSI) KC Bandar Jaya Lampung Tengah? What is the perspective of Islamic Economic Law regarding the restructuring of musyarakah contracts at Bank Syari'ah Indonesia (BSI) KC Bandar Jaya Central Lampung. This study aims to determine the factors of the occurrence of addendum contracts and to find out the practice of restructuring musyarakah contracts in the perspective of Islamic Economic Law and Bank Indonesia Regulations regarding addendums to musyarakah contracts at Bank Syari'ah Indonesia (BSI) KC Bandar Jaya Lampung Tengah. This research is a qualitative research with the type of research